دور إجراءات التدقیق الجبائي في الحد من التھرب الضریبي - ريغي, زين الدين (My University, 2021)
Through this study, we tried to address the theoretical framework of tax evasion: its types, effects, causes, and the methods used to combat it represented in auditing and its various forms،And to support our study, we have studied real cases that were subjected to various types of audit (accounting audit, corrected audit, in-depth audit of the tax situation). In view of the efforts made by the state in general and the fiscal administration in particular, they did not rise to the required level in combating and eliminating this phenomenon, due to several reasons, the most important of which are: Poor coordination between departments and public services The absence of tax awareness among most taxpayers. And other reasons that could impede the process of fiscal audit, so work must be done to develop mechanisms for fiscal audit in order to reduce and eliminate the phenomenon of evasion.
Keywords: tax audit,accounting audit, tax evasion